Impact Analysis and Correlation Study on the Spread of Fake News During Pandemic COVID-19 in Malaysia - Nordin A.Q.; Jamil N.; Zain Z.M.; Ahmad Zawawi M.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Decision making; Fake detection; Forecasting; Control orders; Correlation analysis; Correlation studies; COVID-19; Fake news; Impact analysis; Malaysia; Movement control; Movement control order; Social media; Correlation methods